Uji Daya Hambat Fraksi Rumput Laut Cokelat (Sargassum sp.) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Asmarani, Asmarani; Eso, Amiruddin; Mulyawati, Sufiah Asri (Fakultas Farmasi Universitas Halu Oleo, 2017)
This study aimed to find out the inhibitory fraction of brown seaweed (Sargassum sp.) against the growth of Staphylococcus aureus. This study applied quasi experimental method which used posttest-only control design. Samples used in the form of brown seaweed treatment fraction derived from Desa Bungin Permai Kecamatan Tinanggea Kabupaten Konawe Selatan. The inhibition test was conducted by diffusion agar method used variant concentration (20%, 40%, 60%, 80%, 100%) with three repetitions. Erythromycin as control (+) and DMSO 10% as control (-). The result showed that the fraction of brown seaweed extract has antibacterial properties towards Staphylococcus aureus with the clear zone around the paper disc. The Minimum Inhibitory Concentration (MIC) of n-hexane and ethyl acetate fraction was at the concentration of 20%. Fraction of n-hexane and ethyl acetate have strong inhibition towards Staphylococcus aureus.Keywords: Inhibitory, Staphylococcus aureus, n-hexane, ethyl acetate, MIC